Closed atrium bipolar radiofrequency box lesion for concomitant surgical atrial fibrillation ablation - Pecha, Simon; Petersen, Johannes; Yildirim, Yalin; Bazhanov, Ilia; Reichenspurner, Hermann; Alassar, Yousuf (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn patients with atrial fibrillation (AF) undergoing coronary artery bypass grafting (CABG) or aortic valve replacement (AVR), many surgeons are reluctant to open the left atrium for surgical ablation. However, especially in those with persistent AF, a box lesion isolating the entire posterior left atrial wall may be beneficial. Here, we describe our initial experience with a novel closed atrium bipolar radio-frequency left atrial box ablation technique.MethodsBetween January 2023 and June 2024, 22 patients underwent the closed atrium radio-frequency box lesion set. Left left atrial appendage (LAA) closure was performed using an LAA clip in all patients. We evaluated the technical feasibility, safety, and efficacy of this new concomitant surgical AF ablation approach.ResultsThe mean patient age was 67.9 ± 5.3 years, and 68.2% were male. 12 patients (54.5%) had persistent AF, while 10 (45.5%) had paroxysmal AF. Creation of a complete box lesion from the right side was feasible in 14 patients; in 8 patients, the lesion had to be completed from the left side. No major ablation-related complications occurred. Successful intraoperative LAA closure was confirmed by TEE in all patients. There were no periprocedural strokes, and in-hospital mortality was 0%. Freedom from AF was 86.4% at discharge and 77.2% at a mean follow-up of 12.6 ± 3.9 months.ConclusionThe closed atrium left atrial box lesion technique for surgical treatment of AF concomitant with CABG or AVR is safe and technically feasible. This approach enables complete isolation of the posterior left atrial wall without the need to open the left atrium.